Mechanisms regulating PD-L1 expression in cancers and associated opportunities for novel small-molecule therapeutics - Yamaguchi, Hirohito; Hsu, Jung-Mao; Yang, Wen-Hao; Hung, Mien-Chie (Nature reviews. Clinical oncology, 2022)
Antagonistic antibodies targeting the inhibitory immune-checkpoint receptor PD-1 or its ligand PD-L1 are used to treat a wide range of cancer types and can substantially improve patient survival. Nevertheless, strategies to overcome intrinsic and acquired resistance are required to respectively increase response rates and durations. PD-L1 is often upregulated in various malignancies, and emerging evidence suggests numerous underlying mechanisms involving distinct oncogenic signalling pathways. Thus, specific small-molecule inhibitors have the potential to simultaneously suppress not only a key oncogenic signalling pathway but also PD-L1 expression and/or activity in particular cancers, thereby presenting attractive candidate drugs for combination with existing immune-checkpoint inhibitors and/or other targeted agents. Herein, we summarize advances in understanding the mechanisms regulating PD-L1 expression at the transcriptional, post-transcriptional, translational and post-translational levels in cancers. We describe the roles of the diverse post-translational modifications of PD-L1, including phosphorylation, palmitoylation, glycosylation, acetylation and ubiquitination. Moreover, we discuss the potential use of small-molecule agents to modulate these mechanisms as well as of predictive biomarkers to stratify patients for optimal treatment, and provide our perspective on potential therapeutic strategies to circumvent resistance to conventional anti-PD-1/PD-L1 antibodies.